2019
DOI: 10.2340/16501977-2522
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of healthcare interventions using objective feedback on physical activity: A systematic review and meta-analysis

Abstract: Wearable technology is progressively applied in health care and rehabilitation to provide objective insight into physical activity levels. In addition, feedback on physical activity levels delivered by wearable monitors might be beneficial for optimizing their physical activity. A systematic review and meta-analysis was conducted to evaluate the effectiveness of interventions using feedback on objectively measured physical activity in patient populations. Fourteen studies including 1902 patients were analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 33 publications
0
49
0
2
Order By: Relevance
“…14 It has been suggested that reducing user burden and providing features like goal setting, personalisation and game-like functionality (ie, gamification) may facilitate engagement, promote retention and increase intervention effectiveness. [15][16][17] Existing reviews of apps and trackers have not yet focused on seemingly healthy adults [18][19][20][21][22][23] and technology enabling automated and continuous self-monitoring and feedback, with apps often still requiring users to connect an accelerometer to a computer periodically via a hardware connection. 20 22 24-30 These reviews of older apps and trackers have shown non-significant 22 24 26 or small-to-moderate positive results 20 25 28 with high heterogeneity, often mixing very different types of populations apart from healthy adults (eg, children, 26 elderly 22 27 28 and chronic conditions 20 25 27 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…14 It has been suggested that reducing user burden and providing features like goal setting, personalisation and game-like functionality (ie, gamification) may facilitate engagement, promote retention and increase intervention effectiveness. [15][16][17] Existing reviews of apps and trackers have not yet focused on seemingly healthy adults [18][19][20][21][22][23] and technology enabling automated and continuous self-monitoring and feedback, with apps often still requiring users to connect an accelerometer to a computer periodically via a hardware connection. 20 22 24-30 These reviews of older apps and trackers have shown non-significant 22 24 26 or small-to-moderate positive results 20 25 28 with high heterogeneity, often mixing very different types of populations apart from healthy adults (eg, children, 26 elderly 22 27 28 and chronic conditions 20 25 27 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of initial and continued improvement with GTF, and maintenance of improved values upon removal of GTF, was also observed in Step Count, % Time Jogging, and VO 2 max. Previous research demonstrates similar improvements in physical activity and cardiovascular fitness resulting from interventions incorporating activity trackers and personalized feedback (Braakhuis et al, 2019;Brickwood et al, 2019Brickwood et al, , 2021Ellingson et al, 2019). Furthermore, there is a dose-response relationship between physical activity and major health outcomes, where simply increasing daily step count has a positive impact on mortality and morbidity risk.…”
Section: Discussionmentioning
confidence: 86%
“…Compared to these systems the Activ8 is inexpensive, easy-to-use, and can provide direct feedback. A recent systematic review and meta-analysis has reported that AMs that provide users with ongoing feedback have moderately positive effects on levels of PA [36]. This suggests AMs like the Activ8 would be valuable components of PA promoting programs in the field of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%